Optimisation of SSG (Sodium Starch Glycolate) and Avicel PH 102 in the Formula of Orally Disintegrating Acetaminophen Tablets by Simplex Lattice Design Method - Oktaviani Himmayatin Nisaa; Tri Minarsih (Journal of Science and Technology Research for Pharmacy, 2025)
Background: ODT acetaminophen tablets are an alternative drug therapy for patients who have difficulty in swallowing tablets or capsules. Additional ingredients that play an important role in the ODT tablet formula are disintegrants. The disintegrants used in this study were avicel ph 102 and SSG. The use of disintegrants can help increase the dissolution rate and accelerate the destruction time. Aim: The purpose of this study was to determine the optimum formula of ODT acetaminophen tablets and analyse the effect of SSG and avicel ph 102 on dissolution and disintegration time. Material and Methods: Determination of acetaminophen ODT tablet formula was carried out running in design expert software with the simplex latice design method. Preparation of ODT acetaminophen tablets was carried out by direct felting. The evaluation of ODT acetaminophen tablets was IPC physical evaluation, determination of content, and dissolution. Determination of the optimum formula was done by simplex latice design method. Results: The results showed that all ODT acetaminophen tablet formulas fulfilled all the requirements of the IPC test, physical evaluation, dissolution, and determination of levels according to the Pharmacopoeia VI edition standards. Formula 3 produced the fastest disintegration time of 3 minutes, but the dissolution rate of 100% was reached in the 15th minute. It is suspected that gel formation in the SSG swelling mechanism slowed down the dissolution rate. While formulas 1, 2, and 4 which have a longer disintegration time reached >80% dissolution in the 10th minute. Conclusion: The optimum formula results with the simplex latice design method were SSG 8% and avicel ph 102 7%.  Avicel ph 102 and SSG had the effect of accelerating the destruction time and slowing down the dissolution rate.